The long-run effects of temporarily closing schools: Evidence from Virginia, 1870s-1910s - Paul Winfree (Queen's University Centre for Economic History (QUCEH), 2023)
New hand-collected school administrative data from 1870s Virginia, alongside linked individual US Censusrecords, reveals that temporary school closures had lasting effects on literacy and income in adulthood. Those affected by the closures had lower intergenerational economic mobility, particularly those from low-income backgrounds. The age at which the closures occurred also played a role with younger cohorts more affected by early developmental disruptions and older cohorts more affected by prolonged closures.
Keywords: H75; I21; I24; I26; I28; J62; N31; N91; 330; returns to education; school closures; literacy; economic mobility; wage inequality